2014
DOI: 10.3102/0002831214541670
|View full text |Cite
|
Sign up to set email alerts
|

Parsing Disciplinary Disproportionality

Abstract: In the context of a national conversation about exclusionary discipline, we conducted a multilevel examination of the relative contributions of infraction, student, and school characteristics to rates of and racial disparities in out-of-school suspension and expulsion. Type of infraction; race, gender, and to a certain extent socioeconomic status at the individual level; and, at the school level, mean school achievement, percentage Black enrollment, and principal perspectives all contributed to the probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
241
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 486 publications
(255 citation statements)
references
References 69 publications
10
241
3
1
Order By: Relevance
“…Thus, these results are consistent with the "racial threat hypothesis" in schools suggested by Welch and Payne (2010). One potential weakness of the Skiba et al (2014) study is the setting and context -the data represent a single year in a single U.S. state that serves relatively few FRL-eligible students (fewer than 40%) and very few Black students (8%). Our current study expands on this work by incorporating seven years of student-level panel data in a state that contains a more diverse population (about 21% Black and about 10% Hispanic).…”
Section: Studies Examining the Drivers Of Racial Discipline Gapssupporting
confidence: 75%
See 3 more Smart Citations
“…Thus, these results are consistent with the "racial threat hypothesis" in schools suggested by Welch and Payne (2010). One potential weakness of the Skiba et al (2014) study is the setting and context -the data represent a single year in a single U.S. state that serves relatively few FRL-eligible students (fewer than 40%) and very few Black students (8%). Our current study expands on this work by incorporating seven years of student-level panel data in a state that contains a more diverse population (about 21% Black and about 10% Hispanic).…”
Section: Studies Examining the Drivers Of Racial Discipline Gapssupporting
confidence: 75%
“…Consistent with earlier evidence, we found disproportionate use of exclusionary discipline for Black students, and we also found that these disparities are primarily due to differences in discipline practices across schools, rather than within schools. This result supports the important work of Skiba et al (2014), and builds upon that work by providing analysis of an entire state over seven school years, rather than just one school year.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Disruptive student behaviors that result in school suspensions are categorized as level III or IV infractions [1, 2]. Typically, level III or IV infractions involve the display of explosive, aggressive, or maladaptive patterns of behaviors by students that result in physical harm of other students and/or school personnel.…”
Section: Introductionmentioning
confidence: 99%